Activities of an aqueous plant extract against herpes simplex virus type2 (HSV 2): role in virus replication and progeny yield - Mota Mendes, Ana Rita (2017)
Dissertação de mestrado em Biologia Molecular e Genética, apresentada à Faculdade de Ciências da Universidade de Lisboa, 2015